Childhood bullying and paranoid thinking - Jack, Alexander Henry (2017)
Psychotic phenomena are prevalent in non-clinical populations, with a continuum existing between psychotic-like experiences (PLEs) and incidence of clinical relevance. Phenomena-associated distress often demarcates a threshold whereby individuals seek help, and experiential risk factors are consistent at both ends of the continuum. Increased exposure to stressors may predict the transition from transient, to persistent and impairing psychotic-like symptoms. PLE-specific trajectories have been noted in the literature, with childhood bullying victimisation mooted to predict the development of paranoid thinking; paranoid thinking underlies some expressive violence.